SMRT Sequencing Revealed Mitogenome Characteristics and Mitogenome-Wide DNA Modification Pattern in Ophiocordyceps sinensis - Kang, Xincong; Hu, Liqin; Shen, Pengyuan; Li, Rui; Liu, Dongbo (Frontiers in Microbiology, 2017)
Single molecule, real-time (SMRT) sequencing was used to characterize mitochondrial (mt) genome of Ophiocordycpes sinensis and to analyze the mt genome-wide pattern of epigenetic DNA modification. The complete mt genome of O. sinensis, with a size of 157,539 bp, is the fourth largest Ascomycota mt genome sequenced to date. It contained 14 conserved protein-coding genes (PCGs), 1 intronic protein rps3, 27 tRNAs and 2 rRNA subunits, which are common characteristics of the known mt genomes in Hypocreales. A phylogenetic tree inferred from 14 PCGs in Pezizomycotina fungi supports O. sinensis as most closely related to Hirsutella rhossiliensis in Ophiocordycipitaceae. A total of 36 sequence sites in rps3 were under positive selection, with dN/dS > 1 in the 20 compared fungi. Among them, 16 sites were statistically significant. In addition, the mt genome-wide base modification pattern of O. sinensis was determined in this study, especially DNA methylation. The methylations were located in coding and uncoding regions of mt PCGs in O. sinensis, and might be closely related to the expression of PCGs or the binding affinity of transcription factor A to mtDNA. Consequently, these methylations may affect the enzymatic activity of oxidative phosphorylation and then the mt respiratory rate; or they may influence mt biogenesis. Therefore, methylations in the mitogenome of O. sinensis might be a genetic feature to adapt to the cold and low PO2 environment at high altitude, where O. sinensis is endemic. This is the first report on epigenetic modifications in a fungal mt genome.